PENGENALAN KOSAKATA COVID-19 DALAM BAHASA JEPANG MELALUI AUDIO VISUAL DI SMK SARASWATI 3 DENPASAR - Ni Luh Gede Meilantari; Made Henra Dwikarmawan Sudipa (LOKATARA SARASWATI, 2022)
2020 became a hard year for global society. Since March, 2020, school is closed. All learning process is going by online. On the situation like this, Japanese Literature Study Program, Faculty of Foreign Language, Denpasar Mahasaraswati University would like to held community service, especially at SMK Saraswati 3 Denpasar, as one of high school below Yayasan PR Saraswati Pusat Denpasar (Saraswati Foundation). This service, focused on aiding Japanese learning process, especially on introducing COVID-19 vocabulary in Japanese. Using learning media hopefully can solved online learning problems. Specifically, by using audio visual. In the end of the service, the participants took survey about introducing COVID-19 vocabulary in Japanese using audio visual. From 80 participants, 54 gives feedback and the result is using audio visual as an aid during language learning process is effective, although, the quality of the video should be more attractive to attract students.